Arabidopsis histone deacetylase HD2A and HD2B regulate seed dormancy by repressing DELAY OF GERMINATION 1 - Han, Yongtao; Georgii, Elisabeth; Priego-Cubero, Santiago; Wurm, Christoph J.; Hüther, Patrick; Huber, Gregor; Koller, Robert; Becker, Claude; Durner, Jörg; Lindermayr, Christian (Frontiers in Plant Science, 2023)
Seed dormancy is a crucial developmental transition that affects the adaption and survival of plants. Arabidopsis DELAY OF GERMINATION 1 (DOG1) is known as a master regulator of seed dormancy. However, although several upstream factors of DOG1 have been reported, the exact regulation of DOG1 is not fully understood. Histone acetylation is an important regulatory layer, controlled by histone acetyltransferases and histone deacetylases. Histone acetylation strongly correlates with transcriptionally active chromatin, whereas heterochromatin is generally characterized by hypoacetylated histones. Here we describe that loss of function of two plant-specific histone deacetylases, HD2A and HD2B, resulted in enhanced seed dormancy in Arabidopsis. Interestingly, the silencing of HD2A and HD2B caused hyperacetylation of the DOG1 locus and promoted the expression of DOG1 during seed maturation and imbibition. Knockout of DOG1 could rescue the seed dormancy and partly rescue the disturbed development phenotype of hd2ahd2b. Transcriptomic analysis of the hd2ahd2b line shows that many genes involved in seed development were impaired. Moreover, we demonstrated that HSI2 and HSL1 interact with HD2A and HD2B. In sum, these results suggest that HSI2 and HSL1 might recruit HD2A and HD2B to DOG1 to negatively regulate DOG1 expression and to reduce seed dormancy, consequently, affecting seed development during seed maturation and promoting seed germination during imbibition.